Anxiety, depression and tinnitus: a cross-sectional study about 60 cases - M. Karoui; A. Kchaou; G. Amri; H. Nefzi; R. Kammoun; F. Ellouz (European Psychiatry, 2022)
Introduction Tinnitus is an auditory perception of a “phantom” nature with highly changing features. There is an established correlation between anxiety, depression, sleep disorders and tinnitus.